Pharmacological interventions for patients with chronic primary musculoskeletal pain: disparity between synthesized evidence and real-world clinical practice - Helen Koechlin; Cedric Werdelis; Antonia Barke; Beatrice Korwisi; Roland von Känel; Julia Wagner; Cosima Locher (PAIN Reports)
Introduction:. Chronic primary musculoskeletal pain (CPMP) poses a major problem of public health, with high prevalence rates and economic burden. There is a wealth of clinical trials examining pharmacological interventions for patients with CPMP. Nevertheless, evidence from such trials does not necessarily mirror clinical realities. Objectives:. We aimed to compare data sets from a clinical sample with an randomized controlled trial (RCT)-based sample. Methods:. Both data sets included participants living with CPMP who received pharmacological interventions. The clinical sample was retrieved from electronic health records. The RCT-based sample stemmed from a network meta-analysis project. The following outcomes were used: demographic information, diagnosis-specific data, and pharmacological interventions (categorized according to the World Health Organization [WHO] analgesic ladder). Results:. The clinical sample consisted of 103 patients (mean age: 50.25 years; SD: 14.0) and the RCT-based samples contributed 8665 participants (mean age: 51.97 years; SD: 6.74). In both samples, the proportion of women was higher than that of men (ie, 74.8% vs 58.9%). Psychiatric disorders were the most common comorbidities in the clinic sample but also the most frequent reason for patient exclusion in RCTs. The 2 samples differed significantly in medication classified as WHO III (clinical sample: 12.9%; RCT sample: 23.5%; P = 0.023) and WHO IV (clinical sample: 23.4%; RCT sample: 8.6%; P < 0.001), yet not WHO I and II. Conclusion:. Our findings suggest a disparity between research-based study populations and clinical populations with CPMP. We advocate for future investigations on how to implement robust scientific evidence into real-world clinical practice, with a particular focus on addressing psychiatric comorbidities.